Blockchain technology in~pharmaceutical supply chains: A~transaction cost perspective - Tim Gruchmann; Sara Elgazzar; Ahmed Hussein Ali (Modern Supply Chain Research and Applications, 2023)
Purpose - Adopting new technologies to improve supply chain activities and processes is essential due to increasingly complex and dynamic business environments. Particularly in the pharmaceutical industry, high-quality standards must be met, requiring transparency and visibility in the supply chain. This research aims at investigating the implementation of blockchain technology in the supply chain of an Egyptian pharmaceutical company. Design/methodology/approach - The research applies a single case-study approach building on the theoretical underpinnings of transaction cost economics. Twenty-five semistructured interviews were conducted with pharmacies and employees of the case company to identify the blockchain technologies' potential for pharmaceutical supply in Egypt. Further analyzing the frequencies of the codes, the authors elaborate on specific relationships between the observed practices. Findings - The research revealed the potential benefits of adopting blockchain technology. Transaction costs are indeed positively impacted by reduced contracting costs, processing costs and lead times, also ensuring the safe delivery of medications. However, the findings also highlight obstacles related to running costs, awareness and company culture. Regarding supply chain governance, blockchain technology can enhance collaboration within the supply chain as well as with important stakeholders. Practical implications - Insufficient management of pharmaceutical supply chains (PSC) may affect a company's reputation but also disrupt the patient's healing process due to temperature damage and counterfeit medicines. Blockchain governance, in this vein, can ensure a safer and more reliable supply of pharmaceutical products. For intraorganizational purposes, however, cloud solutions, barcoding and generally digital platforms are rated more frequently than blockchain solutions. Originality/value - The present study contributes to an advanced understanding how blockchain technology supports PSC, particularly in an emerging country context like Egypt. It thereby confirms and extends previous research as well as adds to the theoretical underpinnings of digitalized supply chains.
Keywords: 650; Blockchain technology; Case study; Pharmaceutical sector; Semi-structured interviews; Supply chain digitalization